A descriptive survey on perceptions of selected UP Diliman students on fetish fashion - Bernardo, Queenie Cristalle P.
ABSTRACT This descriptive research aimed to determine how selected students in the University of the Philippines Diliman perceive fetish fashion. A questionnaire was administered to one hundred randomly-selected male and female UP Diliman college students. Both hard-copy survey questionnaires and online survey were utilized to gather data. The questionnaire contained an introductory note about the topic, respondent profile questions, and the survey questions. The questions aimed to gather the respondents' perceptions on fetish fashion under three major categories: awareness, preferences, and acceptability. Data gathered were presented in tables and bar graphs and measures of central tendency were taken to exhibit the concentration and distribution of the data. The survey outcome showed that majority (55%) of the respondents is familiar with fetish fashion prior to the survey, majority (62%) is open to purchasing fetish wear, and majority (64%) is open to wearing fetish clothes and accessories. Findings showed that style and price of the fetish garments are the leading factors that influence the respondents' purchase of the merchandise. Majority (86%) of the respondents consider fetish wear as an aesthetic type of fashion, where as minority (17%) thinks that it is obscene. Based on the survey findings, the most popular means through which respondents learned about fetish fashion is the internet, therefore e-tailing or online advertising is the most The data gained from this study may be used as baseline information for local entrepreneurs planning to venture into the said business. More focused and in-depth future studies on fetish fashion are recommended.